Pola Pertumbuhan Ikan Tempuring (Puntius gemellus) di Sungai Lubuk Bakong Tua Tunu Pangkalpinang, Pulau Bangka - Andi Gustomi; Irma Akhrianti; Rama Supanji (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2019)
Tempuring fish (Puntius gemellus) is a freshwater fish that belongs to the family cyprinidae, genus puntius. Ecobiological information on Tempuring fish at Bangka Island has not been found yet. The Information about Tempuring fish is limited to the study of abundance and diversity of fish species. This research aims to determine growth patterns of Tempuring fish, based on weigth and length relationship aspects. This research used a survey method, and purposive sampling.This research was carried out on the Lubuk Bakong Tua Tunu River in Pangkalpinang City Bangka Island. The results showed that growth pattern of Puntius gemellus is a negative allometric fish (b = 2.25) with a growth model W = 0.056L2.25. The parameters of aquatic environment indicate that the water quality of the measured parameters is still at an adequate threshold for the development of freshwater fish.